The Impact of Scientific Epistemological Beliefs of Sri Lankan Senior Secondary Students on their Approaches to Learning Science: A Structural Equation Modelling Analysis - Prasadini, Lasanthi; Hamid, Junainah Abd.; Khatibi, Ali; Azam, S. M. Ferdous (Asian Journal of Contemporary Education, 2018)
In recent years, there has been a growing interest among researchers on students’ epistemological beliefs and learning approaches which are considered as important predictors of academic achievement. The aim of present study was to ascertain the relationship between Sri lankan senior secondary students’ scientific epistemological beliefs and approaches to learning science. The sample included 415 students from western province of Sri Lanka. The partial least square-structural equation modelling (PLS-SEM) was employed to ascertain the relationships. The results revealed that sophisticated scientific epistemological beliefs of senior secondary students predict their deep learning approaches while less sophisticated scientific epistemological beliefs predict the surface approaches. The findings provide important implications for science learning – teaching process and curriculum reforms.